EXPERIENCE OF IMPLEMENTING NEW TECHNOLOGY TREATMENT OF CHILDREN WITH MPS IN THE RUSSIAN PEDIATRIC PRACTICE - A.A. Baranov; L.S. Namazova-Baranova; A.K. Gevorkyan; V.M. Krasnov; L.M. Kuzenkova; G.A. Kashkaradze; N.D. Vashakmadze; T.V. Podkletnova (Union of pediatricians of Russia, 2011)
The paper is devoted to one of the rare genetically determined diseases - mucopolysaccharidosis. Despite the great achievement of science - the development of the pathogenetic enzyme replacement therapy, many challenges remain. Among them - the lack of timely diagnosis, causing delayed treatment and disease progression, the lack of a national register of patients with common approaches to treatment and rehabilitation of these patients. Objective and subjective obstacles to resolving these problems are demonstrated. The authors developed and represent an efficient system for providing high quality medical care for children with MPS which consists of hospital and rehabilitation phases to colleagues. In addition, the article highlights the issues and postinfuzional reactions during enzyme replacement therapy. Key words: mucopolysaccharidosis, the organization of medical care, diagnosis, treatment, enzyme replacement therapy, the organization of infusion, rehabilitation, supervision, children. (Pediatric Pharmacology. - 2011; 8 (5): 6-12.)